2019
DOI: 10.1017/s2040174419000680
|View full text |Cite
|
Sign up to set email alerts
|

The association between household socio-economic status, maternal socio-demographic characteristics and adverse birth and infant growth outcomes in sub-Saharan Africa: a systematic review

Abstract: AbstractAdverse birth outcomes and infant undernutrition remain the leading causes of morbidity and mortality in sub-Saharan Africa (SSA). Impaired infant growth and development, which often begins during foetal development, may persist during the first 2 years of life and has been associated with higher risks of cardiometabolic diseases. This systematic review assessed the associations between maternal demographic characteristics and household socio-economic status (SES), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 58 publications
3
29
1
Order By: Relevance
“…Among them in India, Ethiopia, Bangladesh, and Pakistan 8,[26][27][28] . This finding reinforces the results of a previous systematic review analyzing publications in three electronic databases (PubMed, Scopus and Science Direct), which found that the socioeconomic disparities of LBW existed in 11 studies published in English 29 .…”
Section: Discussionsupporting
confidence: 90%
“…Among them in India, Ethiopia, Bangladesh, and Pakistan 8,[26][27][28] . This finding reinforces the results of a previous systematic review analyzing publications in three electronic databases (PubMed, Scopus and Science Direct), which found that the socioeconomic disparities of LBW existed in 11 studies published in English 29 .…”
Section: Discussionsupporting
confidence: 90%
“…The socioeconomic, educational and ethnic diversity of the Brazilian population is tremendous, and these characteristics can influence maternal body composition. 45 MUAC must be specific to different populations. The originality of the study was to investigate a cohort of over a 1000 pregnant women from different regions of Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…The socioeconomic, educational and ethnic diversity of the Brazilian population is tremendous, and these characteristics can influence maternal body composition. 45 …”
Section: Discussionmentioning
confidence: 99%
“…Breastfeeding is a positive health behavior that is more prevalent among women with low levels of formal education compared to women with high levels of formal education in LMICs. Because higher levels of formal education are positively correlated with socio-economic status [ 6 ] a higher prevalence of breastfeeding among women with lower compared to higher levels of formal education has helped to reduce the nutrition and health equity gaps between rich and poor children within and across countries. WHO considers ensuring equitable access to breast milk for all infants is a key component of essential newborn care [ 7 ].…”
Section: Introductionmentioning
confidence: 99%